ANALISIS WILLINGNESS TO ACCEPT DANA KOMPENSASI MASYARAKAT SEKITAR TEMPAT PEMROSESAN AKHIR (TPA) CIPEUCANG - Andini Tribuana Tunggadewi; Urmatul Uska Akbar (Jurnal Education and Development, 2023)
TPA Cipeucang in its operational activities faces problems mainly related to the surrounding environment. Some of the environmental problems that arise include water and soil pollution, air pollution, and limited land in the TPA area which then triggers conflicts with the surrounding community. Even so, in reality, TPA has an important role in waste management in urban areas. Regarding conflicts, it is necessary to carry out direct countermeasures for affected communities as compensation in the form of funds or others. Based on that, this study aims to analyze the community's willingness to accept compensation funds and calculate the number of compensation funds that the community is willing to accept. Analysis of the factors that influence the willingness of the community (respondents) to receive compensation funds was carried out using logistic regression analysis. Meanwhile, the analysis of Willingness to Accept (WTA) used as an illustration of the number of funds is carried out using multiple regression analysis. The results of the analysis show that most of the respondents (community) are willing to accept compensation funds with an average WTA value of IDR 254,100 per month.